Mantoux tests of children in household contact with adult acid fast bacilli-positive or -negative pulmonary tuberculosis - Wardah Wardah; Ridwan Muktar Daulay; Emil Azlin; Wisman Dalimunthe; Rini Savitri Daulay (Indonesian Pediatric Society, 2017)
Background Tuberculosis (TB) is the leading cause of mortality and morbidity in developing countries. In children, the major source of TB transmission is adults with pulmonary TB who have acid fast bacilli (AFB)-positive sputum. However, tuberculosis infection can also occur in children in household contact with adults who have AFB-negative pulmonary TB. Objective To compare Mantoux test results and induration diameters in children with adult pulmonary TB household contact who were either positive or negative for AFB, and to assess for possible associations between Mantoux test results with age, family income, and house ventilation in both groups. Methods A cross-sectional study was conducted from January to March 2014. Mantoux test was performed in children aged 3 months to 18 years who had household contact with either AFB-positive or -negative adult pulmonary TB patients. Results A total of 106 children were enrolled in the study. All subjects had household contact with adult pulmonary TB patients who were either AFB-positive (54 children) or AFB-negative (52 children). Mean Mantoux test induration diameters were significantly different between groups (10.9 (SD 6.55) mm vs. 6.2 (SD 5.91) mm, respectively; P=0.001). In addition, there was significantly higher risk of positive Mantoux test in children in contact with adult AFB-positive TB patients than in the AFB-negative group (OR 5.66; 95%CI 2.36-13.59; P=0.0001). However, there were no significant differences in positive Mantoux test results in each of the AFB-positive and -negative groups, with regards to age, family income, or house ventilation. Conclusion Mean Mantoux test induration diameter in children who had household contact with AFB-positive adults is significantly larger than that of the AFB-negative group. Positive Mantoux test results in children are associated with AFB-positive adult TB in the household. There is no association between positive Mantoux test results and age, family income, or house ventilation in both groups. Â